Aplicação de produtos fitossanitários na cultura dos citros utilizando pulverizador envolvente - Carvalho, Giorge França Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The productive sector of the Brazilian citrus industry, the largest at the world in oranges and concentrated citrus juice, faces intense occurrence of pests and diseases. In an attempt to maintain its productivity it makes intense use of pesticides on orchards areas. Place to occurrence, degree of infestation and pest movement have a great influence to crop protection, which the efficiency depends on of distribution of pesticides around canopy. There are many causes that lead to failure of the treatment plant in citrus. Among the main of that the equipment poorly calibrated and rated in terms of size of citrus trees, associated with the project from the sprayers that provide difficulties to better direct sprays to plants. In addition, there are also economic and environmental consequences related to losses by runoff and drift of spraying applied, and sometimes we lose more than 50% of the volume applied. Due that, we elaborate this study to evaluate a surrounding sprayer developed in bases of application rate, spraying distribution and control of Brevipalpus phoenicis (Geijskes, 1939) and fungus Guignardia citricarpa Kiely [Phyllosticta citricarpa (McAlp.) van der Aa .]) at different positions of citrus trees, chosen to constituted greater crop protection problems and to be among the main components in current production costs of citrus in São Paulo. To evaluations will be used two models of tractor-sprayer, a model Arbus 2000® manufactured by Máquinas Agrícolas Jacto S.A., commonly used in citrus in Brazil, considered in this project as the default system (control applied), and another of model Topspray®, manufactured by Herbicat Ltda. equipment, recently launched and developed in a joint with the company and researchers including the authors of this project. The surrounding sprayer brought with it enough characteristics to be considered a viable alternative to use

O setor produtivo da citricultura brasileira, maior do mundo em laranjas e em suco de laranja concentrado, enfrenta intensa ocorrência de pragas e doenças. Visando manter a sua produtividade os produtores recorrem à utilização intensa de agrotóxicos nas áreas de produção. O local de ocorrência, os graus de infestação e de movimentação das pragas têm grande interferência no tratamento fitossanitário, cuja eficácia depende da distribuição do produto pela copa das plantas. São várias as causas que levam ao insucesso do tratamento fitossanitário na cultura de citros. Entre as principais, os equipamentos mal calibrados e mal dimensionados em relação ao porte das plantas de citros, associados ao projeto dos pulverizadores que proporcionam dificuldades para direcionar melhor o jato de calda às plantas. Além destes, há também consequências econômicas e ambientais relacionadas às perdas por escorrimento e por deriva da calda aplicada, verificadas até maiores do que 50% do volume aplicado. Desta forma, elaborou-se o presente projeto com o objetivo de avaliar um pulverizador envolvente, desenvolvido com base na taxa de aplicação, distribuição da calda para avaliar a deposição de calda em diferentes posições das plantas de laranja, a mortalidade do ácaro-da-leprose dos citros Brevipalpus phoenicis (Geijskes, 1939) e o controle do fungo causador da mancha preta dos citros Guignardia citricarpa Kiely [Phyllosticta citricarpa (McAlp.) van der Aa.]), definidos em função de se constituírem nos principais componentes individuais dos atuais custos de produção da citricultura paulista e por serem considerados entre os principais problemas fitossanitários da cultura na atualidade. Para as avaliações serão utilizados dois modelos de pulverizadores de arrasto tratorizados, sendo um o modelo Arbus 2000® fabricado por Máquinas Agrícolas Jacto S.A., de uso corrente na citricultura nacional, considerado ...
Keywords: Cítricos; Cítricos - Doenças e pragas - Controle; Defensivos vegetais; Defensivos vegetais - Tecnologia de aplicação; Produtos químicos agrícolas; Agricultural chemicals